Numerical Simulation and Optimization of the Airflow Field of a Forage Drum Mower - Bei Wu; Tianlin Zuo; Zhuo Li; Huaiyuan Qian; Tianci Huang; Yang Xiang (Applied Sciences, 2023)
The repeated cutting of forage can cause grass breakage and affect the performance of the forage drum mower in harvesting forage. Also, it is worth paying attention to the effect of airflow around the cutter on the cutting and feeding processes. To explore the characteristics of the airflow field around the cutter and optimize the key parameters of the airflow, an analysis of the airflow field of the forage drum mower equipped with twisted blades, tilting discs, and guide plates was conducted through numerical simulation. Furthermore, an orthogonal experiment was carried out by using the numerical simulation model. According to the experimental results, the optimal velocity of the airflow for gathering, lifting, and feeding was reached when the disc speed was 2000 r/min, the blade twist angle was 8°, the disc tilt angle was 4°, and the number of guide plates was 2. On this basis, a prediction model of airflow parameters was constructed, and the parameters of airflow around the cutter were measured on a test bench. According to the measurement results, the results of prediction by the model were consistent with the simulation results. Also, compared with the data of airflow measurement, the average error of the model prediction value was −5.83% for the velocity of the gathering airflow, 2.37% for the velocity of the lifting airflow, and 4.20% for the velocity of the feeding airflow, which demonstrates the reliability of the simulation results and prediction model. The results of this research provide a practical reference for the optimal design of the forage drum mower.